Modifikasi Larutan Buah Bit (Beta vulgaris l.) sebagai Alternatif Pengganti Zat Warna Eosin 2% pada Pemeriksaan Telur Cacing STH (Soil Transmitted Helminths) - Benediktus Adventhia Daeli; Fepy Yulianti; Karolina Rosmiati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Helminthiasis is one of the infections caused by parasites. World Health Organization (WHO) data in 2018 reported 24% of the world's population was infected by Soil-Transmitted Helminths (STH). Worms of this group need soil to be in their infective stage. Eosin 2% is a stain used in the examination of worm eggs. Beetroot (Beta vulgaris L.) is one of the plants widely used as a natural dye. Beetroot contains betacyanin which produces red pigment. This study aimed to identify the feasibility of beetroot as a substitute for eosin to stain worm eggs. This research was true experimental with a static group comparison design. The results showed that the concentration of beetroot solution proportional to the quality of 2% eosin is with a concentration of 95%. Beetroot solution produces color quality with a contrasting background so that the morphology of eggs can be clearly observed. Beetroot extract lasts for 7-day storage at cold temperature.